2014
DOI: 10.1309/ajcp1rebi2uvbhmx
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Aptima and Cervista Tests for Detection of High-Risk Human Papillomavirus in Cervical Cytology Specimens

Abstract: We found poor positive percent agreement between the results of the Aptima and Cervista HPV tests and described an important source of false-positive Cervista results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Munson et al examined 4056 cytology specimens and found an overall concordance between the Cervista and Aptima test results of only 88.7% and that the Cervista test had a much higher number of false‐positive results. In addition, the study from Nolte et al also demonstrated a similar result. The current study assessed the follow‐ups of both the Cervista and Aptima tests in women with LSIL cytology and the results demonstrated that both platforms had similar clinical performance in detecting CIN2 + lesions.…”
Section: Discussionmentioning
confidence: 54%
“…Munson et al examined 4056 cytology specimens and found an overall concordance between the Cervista and Aptima test results of only 88.7% and that the Cervista test had a much higher number of false‐positive results. In addition, the study from Nolte et al also demonstrated a similar result. The current study assessed the follow‐ups of both the Cervista and Aptima tests in women with LSIL cytology and the results demonstrated that both platforms had similar clinical performance in detecting CIN2 + lesions.…”
Section: Discussionmentioning
confidence: 54%
“…Of note is that the Aptima HPV RNA test showed statistically significantly higher specificity for high-grade disease than the HC2 test (159). Subsequent clinical studies have likewise shown that detecting E6/E7 mRNA has similar sensitivity but significantly higher specificity than tests that detect HPV DNA (115,(158)(159)(160)(161)(162)(163)(164)(165)(166)(167)(168)(169).…”
Section: E6/e7 Mrna Pcr (Reverse Transcriptase Pcr)mentioning
confidence: 97%
“…165 However, the Cervista test may have poor specificity compared with other tests for HR HPV. 166,167 The Cervista HPV-16 and -18 genotyping test uses the same cleavase/invader technology.…”
Section: Human Papillomavirusmentioning
confidence: 99%